Thermophysical properties and tribological behavior of hybrid cellulose nanocrystal copper (ii) oxide (cnc-cuo) as lubricant additives - Sakinah, Muhamad Hisham (2022)
Enhancement in the tribological behaviour of piston ring-cylinder liner contact is necessary to reduce the fuel consumption and elongate the engine time deterioration. A novel approach for improving the tribological system and thermophysical properties are dispersing nanoparticles in SAE 40 engine oil. The organic-inorganic nanolubricants is expected to improve the properties of single component nanolubricants in achieving enhancement in thermal properties, rheological properties, stability, thermophysical properties and friction and wear behaviour. The present study aims to evaluate the thermophysical properties of CNC-CuO nanolubricants, investigate the tribological behaviour of CNC-CuO nanolubricant and investigate the optimum condition of the thermophysical properties, friction and wear performance. The nanolubricants was prepared up to 0.9% volume concentration. Thermophysical properties of CNC-CuO nanolubricants were measured at the temperature of 30°C to 90 °C. Meanwhile, tribological properties of the nanolubricants were evaluated for different loads, speeds, temperature and volume concentration. The curve fitting method and Response Surface Methodology (RSM) were used to predict the thermophysical and tribological properties. Response Surface Methodology (RSM) methods were also selected to optimize the thermophysical and tribological friction behaviour. Stability evaluation showed CNC-CuO nanolubricants having an excellent stability condition with no sedimentation observed within a month. It was proven by measuring the zeta potential up to 61.1 mV and maintaining the UV-Vis spectrophotometer's concentration ratio for more than 90%. The viscosity index result shows that the higher the concentration, the VI is improved. VI enhancement is 44.3%-47.12%. Dynamic viscosity, thermal conductivity and specific heat capacity of CNC-CuO nanolubricants increased with volume concentration and decreased with temperature. Maximum enhancement in the dynamic viscosity was 74.81%, respectively, which occurred at the temperature of 90°C at 0.5% concentration. The maximum increase of thermal conductivity was 1.80566 for a volume concentration of 0.1% at 90℃. For specific heat capacity,0.5% is the optimum concentration compared with the base fluid. The proposed correlation of the thermophysical and tribological was considered to predict the properties as the margin of deviation is closer to the points located on the bisector. The results showed that the CNC-CuO nanolubricants reduced the friction coefficient by 48-50%, 33-44%, and 9–13% under boundary, mixed, and hydrodynamic lubrication. It is observed that some severe scuffing and exfoliations phenomenon occurred in SAE 40 sample while light scuffing was found on the CNC-CuO nanolubricant. The extensive scratches happened due to micro-abrasive wear. As an overall conclusion, the addition of CNC-CuO nanoparticles into the engine oil enhances thermophysical properties and tribological behaviour with the optimum concentration at 0.5%.